The Welfare State, Budgetary Pressure and Labour Market Shifts. - Atkinson, A (2000)
Public debate about the welfare state in OECD countries has emphasized the need for reform to meet a twofold set of shocks: budgetary pressure and a labour market shift against unskilled workers. The aim of the paper is to set out a framework for examining the implications of these shocks for the optimal scale of social transfers and, in particular, the impact on different societies, distinguishing a restricted welfare state, labelled "the United States" and a more extensive welfare state, labelled "Continental Europe".